O mal-estar da mulher negra: um percurso pelos aspectos sociais aos aspectos psíquicos - SILVA, Natássia Fortes Braga Portela e (2023)
The malaise is, according to Freudian psychoanalysis, the suffering arising from the difficulties of living in a world of culture, which represses the expression of desire of its subjects. When observing colonial societies, such as Brazil, and the subjects that constitute them, it is understood that racism and sexism, in combination, are specific markers of a reality full of violence against a significant part of the population: black women. According to the most recent publication of the Violence Atlas published by the Institute of Applied Economic Research (IPEA, 2021), 66% of women murdered in 2019 were black, representing the largest number of femicide victims in Brazil. Based on this violent reality to which many of these people and their families are exposed, the following research problem is proposed: in what ways, based on the immanence between social production and the production of subjectivities, can we think about malaise of black women? Therefore, the present work aims to analyze this phenomenon experienced by these women. The specific objectives of the investigation are to think historically and socially about the context of specific oppressions against black women in Brazil; address, according to Psychoanalysis, the discomfort produced in black women in this context; and problematize how these women deal with the effects of such oppression, building new knowledge of themselves and for themselves. The research is of a qualitative nature, where semi-structured interviews were carried out with five (05) participants (self-declared black women and of legal age), and of an exploratory nature, seeking to understand the plurality of experiences lived by these women. Considering that the object of study – the malaise of black women – can be problematized by different perspectives, the theoretical references used for the analysis and discussion of data are predominantly psychoanalytic and black-feminist.